IMPLEMENTASI PENDEKATAN BERBASIS MASALAH (Problem Base Learning) UNTUK MENINGKATKAN HASIL BELAJR BAHASA INDONESIA SISWA KELAS II UPT SD NEGERI SUMURGUNG I TUBAN - Delita Sri Arianti Putri Hendika; Wendri Wiratsiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this research is to help improve the achievement of Indonesian language learning outcomes of grade II UPT SD Negeri Sumurgung I students using a problem-based learning approach. Indonesian language is one of the subjects that students are required to learn. Although this subject is compulsory, the learning outcomes of some students have not yet reached the KKTP. The PTK method or classroom action research is the method used in this research and is carried out in 2 cycles. The stages of the PTK method for each cycle are planning, acting, observing and reflecting. Data collection tools in this research with observation sheets, interview guidelines and test sheets. In the pre-action, students who achieved classical completeness were 44.4% of 9 students in class II. There was an increase after the action in cycle I, namely 66.7% classical completeness, then in cycle II there was an increase again to 88.9%. The conclusion of this research can be stated that the implementation of a problem-based approach can help improve the achievement of Indonesian language learning outcomes of grade II UPT SD Negeri Sumurgung I students on the topic of active and passive verbs.